1995
DOI: 10.1183/09031936.95.08122191
|View full text |Cite
|
Sign up to set email alerts
|

Constrictive bronchiolitis obliterans following gold therapy for psoriatic arthritis

Abstract: This case suggests a possible aetiological role for gold in the pathogenesis of constrictive bronchiolitis obliterans, or alternatively an association between psoriatic arthritis and this inflammatory airway condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
0
10
0
2
Order By: Relevance
“…185 Bronchiolitis obliterans has also been reported in other conditions such as ataxia-telangiectasia, 186 inflammatory bowel disease, 187 localised scleroderma treated with D-penicillamine 188 and psoriatic arthritis treated with gold therapy. 189 …”
Section: Other Causes Of Obliterative Bronchiolitismentioning
confidence: 99%
“…185 Bronchiolitis obliterans has also been reported in other conditions such as ataxia-telangiectasia, 186 inflammatory bowel disease, 187 localised scleroderma treated with D-penicillamine 188 and psoriatic arthritis treated with gold therapy. 189 …”
Section: Other Causes Of Obliterative Bronchiolitismentioning
confidence: 99%
“…The authors found four cases of bronchiolitis. A case of constrictive bronchiolitis obliterans was reported 4 months after initiating intra-muscular chrysotherapy for psoriatic arthritis [187]. Fatal bronchiolitis was also reported 6 months after initiating chrysotherapy in a patient with juvenile rheumatoid arthritis [188].…”
Section: Drug-induced Small Airways Diseasementioning
confidence: 99%
“…The symptoms and chest radiograph changes usually resolve by discontinuing sulfasalazine and starting therapy with prednisone (7). One case of bronchiolitis obliterans with organizing pneumonia has been described in association with sulfasalazine; however, no cases of constrictive bronchiolitis have been described in association with sulfasalazine (8,9). Our patient's respiratory symptoms began before the resumption of sulfasalzine for his musculoskeletal symptoms.…”
Section: Discussionmentioning
confidence: 82%